Monomeric C‐reactive protein via endothelial CD31 for neurovascular inflammation in an ApoE genotype‐dependent pattern: A risk factor for Alzheimer's disease?. Issue 11 (23rd October 2021) - Zhang, Zhengrong; Na, Hana; Gan, Qini; Tao, Qiushan; Alekseyev, Yuriy; Hu, Junming; Yan, Zili; Yang, Jack B.; Tian, Hua; Zhu, Shenyu; Li, Qiang; Rajab, Ibraheem M.; et al.
Abstract: In chronic peripheral inflammation, endothelia in brain capillary beds could play a role for the apolipoprotein E4 (ApoE4)‐mediated risk for Alzheimer's disease (AD) risk. Using human brain tissues, here we demonstrate that the interactions of endothelial CD31 with monomeric C‐reactive protein (mCRP) versus ApoE were linked with shortened neurovasculature for AD pathology and cognition. Using ApoE knock‐in mice, we discovered that intraperitoneal injection of mCRP, via binding to CD31 on endothelial surface and increased CD31 phosphorylation (pCD31), leading to cerebrovascular damage and the extravasation of T lymphocytes into the ApoE4 brain. While mCRP was bound to endothelial CD31 in a dose‐ and time‐dependent manner, knockdown of CD31 significantly decreased mCRP binding and altered the expressions of vascular‐inflammatory factors including vWF, NF‐κB and p‐eNOS. RNAseq revealed endothelial pathways related to oxidative phosphorylation and AD pathogenesis were enhanced, but endothelial pathways involving in epigenetics and vasculogenesis were inhibited in ApoE4. This is the first report providing some evidence on the ApoE4‐mCRP‐CD31 pathway for the cross talk between peripheral inflammation and cerebrovasculature leading to AD risk. Abstract : Our study revealed a novel evidence that links ApoE genotype and cerebrovascular inflammation during peripheral chronic inflammation, which mirrors ApoE4 as a risk factor via endothelial CD31 for AD.